Platelet function and bleeding at different phases of childhood immune thrombocytopenia - Anastasia A. Ignatova (Nature Portfolio, 2021)
Abstract Immune thrombocytopenia (ITP) is believed to be associated with platelet function defects. However, their mechanisms are poorly understood, in particular with regard to differences between ITP phases, patient age, and therapy. We investigated platelet function and bleeding in children with either persistent or chronic ITP, with or without romiplostim therapy. The study included 151 children with ITP, of whom 56 had disease duration less than 12 months (grouped together as acute/persistent) and 95 were chronic. Samples of 57 healthy children were used as controls, while 5 patients with leukemia, 5 with aplastic anemia, 4 with MYH9-associated thrombocytopenia, and 7 with Wiskott-Aldrich syndrome were used as non-ITP thrombocytopenia controls. Whole blood flow cytometry revealed that platelets in both acute/persistent and chronic ITP were increased in size compared with healthy donors. They were also pre-activated as assessed by PAC1, CD62p, cytosolic calcium, and procoagulant platelet levels. This pattern was not observed in other childhood thrombocytopenias. Pre-activation by CD62p was higher in the bleeding group in the chronic ITP cohort only. Romiplostim treatment decreased size and pre-activation of the patient platelets, but not calcium. Our data suggest that increased size, pre-activation, and cytosolic calcium are common for all ITP platelets, but their association with bleeding could depend on the disease phase.